Cancer Therapy: Deep Tumor Penetrating Bioparticulates Inspired Burst Intracellular Drug Release for Precision Chemo‐Phototherapy (Small 12/2018). Issue 12 (25th March 2018) - Wang, Ruoning; Han, Yue; Sun, Bo; Zhao, Ziqiang; Opoku‐Damoah, Yaw; Cheng, Hao; Zhang, Huaqing; Zhou, Jianping; Ding, Yang
Abstract : In article number1703110, Jianping Zhou, Yang Ding, and co‐workers introduce a bioinspired particulate formulated with whole components of native HDLs and decorated with tumor‐penetrating peptide iRGD. This proposal of penetrated HDLs (pHDLs) shares artificially endowed functions, leading to higher tumor accumulation and enhanced cellular uptake, burst intracellular drug release, and precision chemo‐phototherapy without causing appreciable adverse effects.